2022
DOI: 10.1177/09603271221136206
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the toxic effects of thimerosal and/or aluminum hydroxide in SH-SY5Y cell line

Abstract: In this study, we aimed to evaluate possible toxic effects of thimerosal, aluminum and combination of thimerosal and aluminum in SH-SY5Y cells. Inhibitory concentrations were determined by MTT assay; reactive oxygen species (ROS) were determined by a fluorometric kit and antioxidant/oxidant parameters were measured by spectrophotometric kits. Nuclear factor erythroid 2-associated factor 2 (Nrf2), norepinephrine (NE), dopamine transporter (DAT) and dopamine beta β-hydroxylase (DBH) levels were measured by sandw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…In our study, we showed that VCO affects the dopaminergic system positively and the dopamine activity is regulated. Our results are consistent with our previous study, which we have shown that Al exposure dysregulated the dopamine neurotransmitter function (Öztürk et al, 2022). Currently, we suggest that treatment by VCO may reverse this phenomenon and regulate the dopaminergic activity in neuroblastoma cells exposed to both Al.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In our study, we showed that VCO affects the dopaminergic system positively and the dopamine activity is regulated. Our results are consistent with our previous study, which we have shown that Al exposure dysregulated the dopamine neurotransmitter function (Öztürk et al, 2022). Currently, we suggest that treatment by VCO may reverse this phenomenon and regulate the dopaminergic activity in neuroblastoma cells exposed to both Al.…”
Section: Discussionsupporting
confidence: 94%
“…The competitive inhibition reaction between the HRP‐labeled dopamine and dopamine without the antibody led to a color change that was inversely proportional to the amount of DA present in the samples. ODs were measured at 450 nm, and the concentration of DA in the samples was expressed in ng/ml (Öztürk et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, we found Nrf2 mRNA expression to be significantly lower in the frontal cortex of ASD subjects 110 . In vitro, aluminum hydroxide increases Nrf2 expression in conjunction with its induction of oxidative stress 111 . Moreover, aluminum citrate inhibits, as well as downregulates the expression of the xCT cystine/glutamate antiporter 112 .…”
Section: Vulnerable Subpopulations: Autism Spectrum Disorder (Asd) An...mentioning
confidence: 97%